Determination of elements in rice using laser induced breakdown spectroscopy and atomic absorption spectroscopy - Abdul Wahid, Rahmat (2014)
Laser-induced breakdown spectroscopy (LIBS) technique offers simplicity, real-time analysis and requires minimal or no sample preparation, in contrast to conventional method of elemental analysis. In this research, LIBS technique was used for elemental analysis of rice. Conventional atomic absorption spectroscopy (AAS) technique was used for validation of LIBS findings and quantification of elements. Twelve commercially available rice of different varieties, grain sizes and polishing rates were selected as samples. Pellets from each sample were prepared for qualitative analysis using LIBS technique. An ungated LIBS system was constructed using Nd:YAG pulsed laser as the excitation source and an atomic emission detection system consist of optical fibre, spectrometer and computer. Fifty spectra from different spots on each pellet were averaged and analyzed using OriginPro 8.5 for baseline removal and peak findings. The system developed proved to be reliable for the detection of elements since the plasma produced satisfied the criteria for local thermodynamic equilibrium. This is confirmed in the calculation of plasma temperature and electron density. The elements in rice detected in this work are magnesium, calcium, potassium, sodium, hydrogen and oxygen. For the AAS technique, rice samples were digested with aqua regia solution and analyzed with PerkinElmer AAnalyst 400 spectrometer. Calcium and potassium in the samples were validated using AAS technique. Quantitative analysis from AAS technique shows that samples from brown rice have higher calcium (209.22 mg·kg-1) and potassium (2757.96 mg·kg-1) concentration compared to others